Vitamin D Status and Its Influence on the Health of Preschool Children in Hangzhou - Chen, Zhaojun; Lv, Xi; Hu, Wensheng; Qian, Xia; Wu, Ting; Zhu, Yunxia (Frontiers in Public Health, 2021)
Objective: Vitamin D deficiency and insufficiency in children are global public health problems. However, few studies have focused on vitamin D status in healthy preschool children, especially in Asia. This study aimed to investigate vitamin D status and host-related factors in healthy preschool children in Hangzhou to analyze the impact of low vitamin D levels (<30 ng/mL) on health outcomes (obesity, early childhood caries, and respiratory tract infections). Methods: A total of 1,510 healthy children aged 24–72 months from 15 kindergartens in Hangzhou were included. Data on the children's gender, age, body mass index (BMI), caries, and blood samples available for vitamin D analysis were collected from June to August 2018. A total of 325 children aged 36–48 months took part in a survey on the frequency of respiratory tract infections in the last year. Results: The children's mean 25(OH)D level was 28.01 ± 7.29 ng/mL. A total of 11.4% of the children had vitamin D deficiency, and 52.6% had vitamin D insufficiency. Only 36.0% had vitamin D sufficiency. No significant difference was found by gender or BMI group. However, children in the obesity group had the highest prevalence of vitamin D deficiency and the lowest 25(OH)D levels. A significant negative correlation was found between the 25(OH)D level and child age (r = −0.144, p < 0.001). Regression analysis showed that the children’s 25(OH)D levels decreased by 0.17 ng/mL per month with age. In addition, children with low vitamin D levels might increase the risk of obesity and early childhood caries. Multiple linear regression indicated that the number of caries in children increased by 0.08 per 1-ng/mL decrease in the 25(OH)D level (β = −0.08, p < 0.001). Conclusion: Vitamin D deficiency/insufficiency is a serious problem among healthy preschool children in Hangzhou. Public health policies or interventions should be implemented to ensure that preschool children have adequate vitamin D to reduce the risk of related diseases.